Presentation is loading. Please wait.

Presentation is loading. Please wait.

CHAPTER 2 RevIEw precalculus.

Similar presentations


Presentation on theme: "CHAPTER 2 RevIEw precalculus."— Presentation transcript:

1 CHAPTER 2 RevIEw precalculus

2

3 y = (x+2)2

4

5 y = (x-2)2 -1

6

7 y = -(x+1)2 + 3

8 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s s , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.

9 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s s , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.

10 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s s , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.

11 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s s , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth. 59.4 MPH

12 5) f(x) = x2 - 16

13 5) f(x) = x2 - 16 = (x )(x )

14 5) f(x) = x2 - 16 = (x - 4)(x + 4)

15 5) f(x) = x2 - 16 = (x - 4)(x + 4) zeros: 4, -4

16 6) f(x) = x2 + 12x + 36

17 6) f(x) = x2 + 12x + 36 = (x )(x )

18 6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6)

19 6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6) zeros: -6, -6

20 7) f(x) = 2x2 - 14x + 24

21 7) f(x) = 2x2 - 14x + 24 = 2( )

22 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12)

23 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x )(x )

24 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3)

25 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3) zeros: 4, 3

26 8) f(x) = x4 - x3 - 20x2

27 8) f(x) = x4 - x3 - 20x2 = x2( )

28 8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x)

29 8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x )(x )

30 8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x + 4)(x - 5)

31 8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5)

32 8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5) zeros: 0, 0, -4, 5

33 Find a polynomial with the following zeros.
9) -7, 2

34 Find a polynomial with the following zeros.
9) -7, 2 (x - -7)(x - 2)

35 Find a polynomial with the following zeros.
9) -7, 2 (x - -7)(x - 2) (x + 7)(x - 2)

36 Find a polynomial with the following zeros.
9) -7, 2 (x - -7)(x - 2) (x + 7)(x - 2) x2 - 2x + 7x - 14

37 Find a polynomial with the following zeros.
9) -7, 2 (x - -7)(x - 2) (x + 7)(x - 2) x2 - 2x + 7x - 14 x2 + 5x - 14

38 10) 0, 4

39 10) 0, 4 (x - 0)(x - 4)

40 10) 0, 4 (x - 0)(x - 4) x(x - 4)

41 10) 0, 4 (x - 0)(x - 4) x(x - 4) x2 - 4x

42 What does the graph of each function look like? (circle two for each)
11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right

43 What does the graph of each function look like? (circle two for each)
11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right

44 What does the graph of each function look like? (circle two for each)
11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right

45 12) f(x) = 0.5x3 + 2x rises to the left rises to the right
falls to the left falls to the right

46 12) f(x) = 0.5x3 + 2x rises to the left rises to the right
falls to the left falls to the right

47 12) f(x) = 0.5x3 + 2x rises to the left rises to the right
falls to the left falls to the right

48 13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right
falls to the left falls to the right

49 13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right
falls to the left falls to the right

50 13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right
falls to the left falls to the right

51 14) f(x) = -x5 - 7x + 10 rises to the left rises to the right
falls to the left falls to the right

52 14) f(x) = -x5 - 7x + 10 rises to the left rises to the right
falls to the left falls to the right

53 14) f(x) = -x5 - 7x + 10 rises to the left rises to the right
falls to the left falls to the right

54 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3)

55 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) 2x x3 - 3x2 - 50x + 75

56 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x x3 - 3x2 - 50x + 75

57 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x x3 - 3x2 - 50x + 75 2x3 - 3x2

58 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x x3 - 3x2 - 50x + 75 2x3 - 3x2

59 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x x3 - 3x2 - 50x + 75 2x3 - 3x2 x + 75

60 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x 2x x3 - 3x2 - 50x + 75 2x3 - 3x2 x + 75

61 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x 2x x3 - 3x2 - 50x + 75 2x3 - 3x2 x + 75 - 50x + 75

62 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x 2x x3 - 3x2 - 50x + 75 2x3 - 3x2 x + 75 - 50x + 75

63 Use long division to simplify.
15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x 2x x3 - 3x2 - 50x + 75 2x3 - 3x2 x + 75 - 50x + 75

64 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

65 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

66 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

67 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5) 3

68 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5) 15 3

69 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5) 15

70 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

71 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

72 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

73 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5)

74 Use synthetic division to simplify.
16) (3x3 - 17x2 + 15x - 25) / (x - 5) 3x2 - 2x + 5

75 17) (2x3 + 14x2 - 20x + 7) / (x + 6)

76 17) (2x3 + 14x2 - 20x + 7) / (x + 6)

77 17) (2x3 + 14x2 - 20x + 7) / (x + 6)

78 17) (2x3 + 14x2 - 20x + 7) / (x + 6)

79 17) (2x3 + 14x2 - 20x + 7) / (x + 6) 2x2 + 2x x+6

80 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor

81 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor

82 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor

83 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor

84 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor x2 + 8x + 7

85 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor x2 + 8x + 7 (x + 1)(x + 7)

86 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor x2 + 8x + 7 (x + 1)(x + 7) (x - 4)(x + 1)(x + 7)

87 Write in completely factored form. Then find all zeros.
18) f(x) = x3 + 4x2 - 25x Hint: (x - 4) is a factor x2 + 8x + 7 (x + 1)(x + 7) (x - 4)(x + 1)(x + 7) zeros: 4, ,

88 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors

89 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors

90 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors

91 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8

92 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8

93 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8

94 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8

95 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8 x2 - 3x - 4

96 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8 x2 - 3x - 4 (x - 4)(x + 1)

97 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8 x2 - 3x - 4 (x - 4)(x + 1) (x - 4)(x + 1)(x + 2)(x - 3)

98 19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
x3 - x2 - 10x - 8 x2 - 3x - 4 (x - 4)(x + 1) (x - 4)(x + 1)(x + 2)(x - 3) zeros: 4, , ,

99 Write each complex number in standard form.
20) (3 + 2i) + (5 + i)

100 Write each complex number in standard form.
20) (3 + 2i) + (5 + i) 8 + 3i

101 21) (3 + 2i)(5 + i)

102 21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2

103 21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2 i + 2i2

104 21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2 i + 2i2 i + 2(-1)

105 21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2 i + 2i2 i + 2(-1) i

106 22) (3 + 2i) (5 + i)

107 22) (3 + 2i) * (5 - i) (5 + i) * (5 - i)

108 22) (3 + 2i) * (5 - i) = i + 10i - 2i2 (5 + i) * (5 - i) = i - 5i - i2

109 22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1)

110 22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1)

111 22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1) =
26

112 22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1) =
26 i

113 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6

114 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6

115 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6

116 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6

117 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6

118 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6

119 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6 =

120 Find all zeros. Then rewrite the function in completely factored form.
23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6 =

121 24) f(x) = x2 + 2x + 4

122 24) f(x) = x2 + 2x + 4 Quadratic Formula

123 24) f(x) = x2 + 2x + 4 Quadratic Formula > Magic Happens

124 24) f(x) = x2 + 2x + 4 Quadratic Formula > Magic Happens >

125 24) f(x) = x2 + 2x + 4 Quadratic Formula > Magic Happens >

126 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4

127 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4

128 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4

129 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4

130 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 3x3 - 7x2 + 14x - 4

131 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 / 3x3 - 7x2 + 14x x2 - 6x + 12

132 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 / 3x3 - 7x2 + 14x x2 - 6x + 12 Quadratic Formula

133 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 / 3x3 - 7x2 + 14x x2 - 6x + 12 Quadratic Formula > Magic Happens

134 Quadratic Formula -------> Magic Happens ------->
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 / 3x3 - 7x2 + 14x x2 - 6x + 12 Quadratic Formula > Magic Happens > x = x =

135 Quadratic Formula -------> Magic Happens ------->
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 / 3x3 - 7x2 + 14x x2 - 6x + 12 Quadratic Formula > Magic Happens > x = x =

136 26) f(x) = x3 - 4x2 + 6x - 4

137 26) f(x) = x3 - 4x2 + 6x - 4

138 26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____

139 26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____ Synthetic Division

140 26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____ Synthetic Division > x2 - 2x + 2

141 26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____ Synthetic Division > x2 - 2x > Quadratic Formula

142 26) f(x) = x3 - 4x2 + 6x - 4 2, 1 + i, 1 - i Synthetic Division > x2 - 2x > Quadratic Formula

143 26) f(x) = x3 - 4x2 + 6x - 4 2, 1 + i, 1 - i (x - 2)(x i)(x i) Synthetic Division > x2 - 2x > Quadratic Formula

144 Find a polynomial with the following zeros.
27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x i)(x i) x2 - 2x + 3ix

145 Find a polynomial with the following zeros.
27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x i)(x i) x2 - 2x + 3ix - 2x i

146 Find a polynomial with the following zeros.
27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x i)(x i) x2 - 2x + 3ix - 2x i - 3ix + 6i - 9i2

147 Find a polynomial with the following zeros.
27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x i)(x i) x2 - 2x + 3ix - 2x i - 3ix + 6i - 9i2 x2 - 2x + 3ix - 2x i - 3ix + 6i - 9(-1)

148 Find a polynomial with the following zeros.
27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x i)(x i) x2 - 2x + 3ix - 2x i - 3ix + 6i - 9i2 x2 - 2x + 3ix - 2x i - 3ix + 6i - 9(-1) x2 - 4x

149 Find a polynomial with the following zeros.
27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x i)(x i) x2 - 2x + 3ix - 2x i - 3ix + 6i - 9i2 x2 - 2x + 3ix - 2x i - 3ix + 6i - 9(-1) x2 - 4x x2 - 4x + 13

150 28) 0, 3, 5i, -5i

151 28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i)

152 28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 )

153 28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 ) ( x2 - 3x ) (x2 + 25)

154 28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 ) ( x2 - 3x ) (x2 + 25) x4 + 25x2 - 3x3 - 75x

155 28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 ) ( x2 - 3x ) (x2 + 25) x4 + 25x2 - 3x3 - 75x x4 - 3x3 + 25x2 - 75x

156 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 29)

157 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 29) HA: y = -1 VA: x = -3 Holes: none

158 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 30)

159 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 30) HA: y = 4 VA: x = 8 Holes: none

160 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 31)

161 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 31) HA: y = 0 VA: x = -3, x = 6 Holes: none

162 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 32)

163 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 32) HA: y = 0 VA: x = -1, x = 1 Holes: none

164 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 33)

165 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 33) HA: y = 3 VA: none Holes: none

166 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 34) hint: this one has a hole

167 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 34) hint: this one has a hole HA: y = 1 VA: x = -1 Holes: x = 1 (x - 4)(x - 1) (x + 1)(x - 1)

168 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 35) hint: this one has a hole

169 Find the horizontal asymptotes, vertical asymptotes, and holes
for each rational function. 35) hint: this one has a hole HA: y = 1 VA: x = -1.5 Holes: x = 3 (2x - 1)(x - 3) (2x + 3)(x - 3)

170 36). This table shows the amounts A (in dollars) spent per
36) This table shows the amounts A (in dollars) spent per person on the internet in the United States from 2000 to Use a graphing calculator to create a scatter plot of the data. Let t represent the year, with t = 0 corresponding to 2000. a) Calculate a quadratic regression line to fit the data. What is its equation? b) Based on your quadratic model, approximate how much was spent on each person in 2008. Year Amount, A (in hours) 2000 3492 2001 3540 2002 3606 2003 3663 2004 3757 2005 3809

171 36). This table shows the amounts A (in dollars) spent per
36) This table shows the amounts A (in dollars) spent per person on the internet in the United States from 2000 to Use a graphing calculator to create a scatter plot of the data. Let t represent the year, with t = 0 corresponding to 2000. a) Calculate a quadratic regression line to fit the data. What is its equation? f(x) = 2.36t t b) Based on your quadratic model, approximate how much was spent on each person in 2008. Year Amount, A (in hours) 2000 3492 2001 3540 2002 3606 2003 3663 2004 3757 2005 3809

172

173

174

175

176

177

178

179

180

181

182

183

184

185

186

187

188

189

190

191

192


Download ppt "CHAPTER 2 RevIEw precalculus."

Similar presentations


Ads by Google